2015
DOI: 10.1186/s12967-015-0652-4
|View full text |Cite
|
Sign up to set email alerts
|

The nutrigenetic influence of the interaction between dietary vitamin E and TXN and COMT gene polymorphisms on waist circumference: a case control study

Abstract: BackgroundAbdominal obesity (AO) is a common modifiable risk factor for certain non-communicable diseases associated with enhanced oxidative stress (OS). The objective of this work was to investigate whether the interaction between antioxidant vitamin intake and OS-related polymorphisms modulates gene-associated anthropometry in a Spanish population.MethodsA total of 246 subjects with AO, and 492 age and gender matched non-AO subjects were included in the study. Anthropometric, biochemical, and OS parameters, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 57 publications
1
19
0
Order By: Relevance
“…The study shows a negative correlation between Vitamin E and waist circumference, similar to other studies [ 28 ]. The relationship between this vitamin and increased adiposity has been investigated in the literature because of its functions in reducing adipose tissue fibrosis, inflammation, and oxidative stress due to its anti-inflammatory and antioxidant capacity.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The study shows a negative correlation between Vitamin E and waist circumference, similar to other studies [ 28 ]. The relationship between this vitamin and increased adiposity has been investigated in the literature because of its functions in reducing adipose tissue fibrosis, inflammation, and oxidative stress due to its anti-inflammatory and antioxidant capacity.…”
Section: Discussionsupporting
confidence: 91%
“…The significant negative correlation between retinol and glucose observed in our study is similar to the findings of Teske and co-workers (2014) [ 26 ] in a study conducted with children and adolescents with obesity. Hyperglycemia is one of the conditions of obesity that contributes to oxidative stress, favoring the formation of reactive oxygen species, which increases the expense of micronutrients with antioxidant function [ 28 ]. In addition, since it is a condition related to type 2 diabetes mellitus, and to insulin resistance, there is evidence that retinol can increase insulin sensitivity by promoting its increased signaling [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…COMT (ENSP00000354511) has also been predicted to be a co-related gene for both obesity and psychiatric diseases. A case study [ 93 ] in 2015 validated that the polymorphisms of COMT may be correlated with obesity occurrence. Further study on COMT confirmed that such gene turns out to be one of the potential pathogenic gene for Parkinson disease, validating the efficacy and accuracy of our prediction.…”
Section: Discussionmentioning
confidence: 99%
“…Dietary factors may influence gene expression [ 11 12 13 ]. One case control study [ 11 ] reported a nutrigenetic interaction between dietary vitamin E and thioredoxin and catechol-Omethyltransferase gene polymorphisms on waist circumference. Dietary factors may also alter the risk of inflammatory disease.…”
Section: Introductionmentioning
confidence: 99%